Agricultural fundamentalism in Greece: an empirical analysis - Βελέντζας Κώστας; Κατρανίδης Στέλιος Δ.; Κόρδας Γρηγόρης (SPOUDAI Journal of Economics and Business, 2003)
In the present paper an effort is being made to determine and study the factors that contribute to the formation of attitudes in Greek society on an important issue such as the necessity and the type of state intervention in the agricultural sector. Another aspect that is examined is to what extent these views differ among various social groups. For the purposes of the present study, we analysed answers given by a sample of 711 individuals and we examined the significance that the social and personal characteristics of the respondents have, in shaping up their views on state intervention in the Greek agricultural sector. According to the research results, state intervention in the agricultural sector enjoys greater support by people with a farming occupation or with relatives actively involved in farming, as well as by younger persons. On the other hand, the degree of acquired information regarding the real economic importance of the agricultural sector influences negatively the individuals' viewpoint towards state intervention in the agricultural economy JEL: Classification: A13, Al4, Q18